Youth Justice and Education: A Typology of Educational Approaches to the Resocialisation of Young Offenders in Spain - Mejías, Felipe Morente; Benítez, Inmaculada Barroso; Davison, Charlie; Green, Gillian (International Journal of Criminology and Sociology, 2013)
The Young Offenders Act that entered Spanish law in 2000 represents a significant attempt to place personalised educational programmes for young people with social/criminal problems at the centre of policy and practice. This paper examines the teams and educational programmes designed to manage and implement the goal of ‘re-socialisation’ enshrined in the Act. This paper focuses on an analytical typology of the educational styles used at young offenders institutions in Spain. The analysis highlights the differences between styles in relation to the key underlying objectives of social reorientation and citizen empowerment. The wide range of models experimented with in different Spanish regions has great relevance to youth justice systems in other countries. For example, the typology we put forward has concrete implications for recent developments in England, in the light of moves towards establishing a national network of “Secure Colleges” for convicted young people.